SRATEGI MANAJEMEN RESIKO DALAM MENGHADAPI KETIDAKPASTIAN DI PASAR GLOBAL - Suhada; Mayla Humaira As-syiva; Eriana Saprida; Arsyadona (JOURNAL SAINS STUDENT RESEARCH, 2025)
Uncertainty in global markets is a central issue in modern business management due to deep globalization. This uncertainty creates challenges for companies in all sectors due to rapid changes in consumer trends, government regulations, exchange rate fluctuations and geopolitical conditions. The aim of this journal is to provide an in-depth understanding of risk management in global markets as well as explore relevant risk management strategies, which are important for the future success of organizations in a complex global business environment. This research methodology combines a qualitative approach with literature analysis. By carrying out comprehensive risk identification, companies can determine appropriate mitigation steps. An integrated approach, which includes product diversification, hedging, technological innovation and corporate social responsibility, helps companies not only survive but also thrive. Thus, developing adaptive risk management strategies is critical to long-term success in dynamic global markets.